Load control system in sport training - Szmuchrowski, L.; Silva, H. R.; Kosmol, A. (International Journal of Computer Science in Sport, 2002)
To systemize and control training loads and recovery times, according to an athlete`s peculiarities and specific aims are important tasks of sport science. Relied on sport training concepts, a system to register and analysis of training loads - RAC - is proposed. RAC System is a new technology that enables a global study of sport training by a three-dimensional model of load components (exercise, intensity and duration of stimulus). Time is the single unit used to register applied load. By this unit, other parameters are studied and organized. Different activities are registered according to their arrangement in Mean Catalogs. The catalogs are lists of exercises and training methods, specific for each sport. The effective time of applied load is registered by means of the software TRAINING ORGANIZER. This software enables for each mean of training the study of load parameters, such as magnitude, structure and dynamics. In addition, another software - MULTISPRINT -offers computer tests for performance evaluation based on mechanic parameters, like time and space. With those softwares, RAC provides an analysis of adaptation process on performance enhancing. Thus, RAC System is a set of tools that supplies objective informations about athlete's condition and the periods of training. As a computer system, RAC is an effective alternative to control performance outcome. Online vision of load parameters improves efficiency on training adjustment.